2012
DOI: 10.2478/s11756-012-0010-4
|View full text |Cite
|
Sign up to set email alerts
|

New record of the fungus Coniochaeta prunicola on peaches from Slovakia

Abstract: The first record of Coniochaeta prunicola Damm & Crous (Coniochaetales, Sordariomycetes, Ascomycota) as a pathogen of Persica vulgaris Mill. described and illustrated from Nitra district, Slovakia. C. prunicola was isolated from symptomatic leaves of host tree and based on morphological attributes identified for the first time as a causative agent of peach tree damage. C. prunicola is characterized by dark brown ascomata clothed with setae, the fasciculate, unitunicate, cylindrical asci and broadly almond-shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…These isolates are closely related to an isolate from a native lichen in North Carolina (isolate NC1642), which we also characterize here. We compare 9055 and 9094 with two closely related species: C. prunicola, which is associated with wood necrosis in stonefruit trees in South Africa (Damm et al 2010; see also Ivanová & Bernadovičová 2012), and C. cephalothecoides, originally isolated from soil in Japan (Kamiya et al 1995; see also Han et al 2017). Finally, we discuss the challenge of identifying new species in the context of fungal ecology surveys, which often rely only on a single locus and can misidentify taxa based on their closest matches in public databases or simple comparisons of barcode sequences.…”
Section: Introductionmentioning
confidence: 99%
“…These isolates are closely related to an isolate from a native lichen in North Carolina (isolate NC1642), which we also characterize here. We compare 9055 and 9094 with two closely related species: C. prunicola, which is associated with wood necrosis in stonefruit trees in South Africa (Damm et al 2010; see also Ivanová & Bernadovičová 2012), and C. cephalothecoides, originally isolated from soil in Japan (Kamiya et al 1995; see also Han et al 2017). Finally, we discuss the challenge of identifying new species in the context of fungal ecology surveys, which often rely only on a single locus and can misidentify taxa based on their closest matches in public databases or simple comparisons of barcode sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the isolates found in our propolis samples belonged to the genera Coniochaeta, Aspergillus , Penicillium , Cladosporium , and Fusarium . Among the dominant genera in the obtained collection , Coniochaeta is characterized by the ability to grow in an acidic environment [ 47 ] and members of this genus have been previously isolated from young plants [ 48 ], floral nectar [ 49 ], and fruit trees [ 50 ]. In this way, their origin could be attributed to honeybees' gut microbiota as a source of acidophilic microorganisms and/or from plant sources during the foraging season.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, two strains isolated as endophytes from healthy, mature foliage of Platycladus orientalis (Cupressaceae) in an arboretum in Arizona, USA were found to be affiliated with, but distinct from, the ex-type and paratype of C. prunicola (CBS 120875 and CBS 121445, respectively;Damm et al 2010). The strains representing C. prunicola occurred in association with necrotic wood of stonefruit trees in South Africa (Prunus armeniaca and P. persica, respectively) (see Damm et al 2010; see also Ivanová & Bernadovičová 2012). Harrington et al ( 2019) concluded that the endophytic strains of interest from Arizona represented a novel species therein described as C. endophytica.…”
Section: Introductionmentioning
confidence: 99%